Hubungan Pola Perilaku Hidup Sehat dengan Prestasi Akademik Mahasiswa Keperawatan[Correlation Between Healthy Lifestyle With The Academic Performance Of Nursing Students] - Riama Marlyn Sihombing; Ed Rosi Pratama (Universitas Pelita Harapan, 2018)
Maintaining a healthy lifestyle pattern is a challenge for health practitioners. As a prospective member of the health profession with the greatest number in Indonesia, nursing students are expected to have knowledge and adequate healthy living behavior in order to become a role model for the community. The pattern of healthy life behavior affects the value of student achievement. This study aims to determine the relationship of healthy behavior patterns with the academic achievement of nursing students. The research design is using quantitative descriptive which is data collection cross sectional. The population is a student of the Faculty of Nursing and Health Sciences at the University X. The sample of the study of 179 students is taken based on purposive sampling with inclusion criteria of students of class 2015 active and willing to be a respondent. The instrument in the form of Health Promoting Lifestyle Profile II (HPLP-II) questionnaire that has been adapted in Indonesian consists of 22 items of questions on a Likert scale and a cumulative grade point. The result of the research shows that more than half of the students (59,8%) have unhealthy behavior pattern (M = 2,474, SD = 0,382) and most (87,7%) students have very satisfactory academic achievement. The statistical test showed that there was no correlation between healthy behavior pattern with student achievement (P = 0,944 > 0,05). Further research is expected to examine the factors that influence healthy behavior patterns with the academic achievement of nursing students.BAHASA INDONESIA Mempertahankan pola perilaku hidup sehat merupakan tantangan bagi praktisi di bidang kesehatan. Sebagai calon anggota profesi kesehatan dengan jumlah terbanyak di Indonesia, mahasiswa keperawatan diharapkan mempunyai pengetahuan dan perilaku hidup sehat yang memadai agar dapat menjadi role model bagi masyarakat. Pola perilaku hidup sehat berdampak pada nilai prestasi akademik mahasiswa. Penelitian ini bertujuan untuk mengetahui hubungan pola perilaku hidup sehat dengan prestasi akademik mahasiswa keperawatan. Desain penelitian menggunakan deskriptif kuantitatif yang pengumpulan datanya secara cross sectional. Populasi adalah mahasiswa Fakultas Keperawatan dan Ilmu Kesehatan di Universitas di bagian Barat Indonesia. Sampel penelitian sebanyak 179 mahasiswa diambil berdasarkan purposive sampling dengan kriteria inklusi mahasiwa angkatan 2015 yang aktif kuliah dan bersedia menjadi responden. Instrumen berupa kuesioner Health Promoting Lifestyle Profile II (HPLP-II) yang telah diadaptasi dalam bahasa Indonesia terdiri dari 22 item pertanyaan dalam skala Likert dan indeks prestasi kumulatif. Hasil penelitian menunjukkan lebih dari setengah (59,8%) mahasiswa mempunyai pola perilaku hidup tidak sehat (mean = 2,474, SD = 0,382) dan sebagian besar (87,7%) mahasiswa memiliki prestasi akademik yang sangat memuaskan. Uji Mann-Whitney U didapatkan tidak ada hubungan pola perilaku hidup sehat dengan prestasi akademik mahasiswa (P = 0,944 > 0,05). Penelitian selanjutnya diharapkan dapat meneliti faktor-faktor yang mempengaruhi pola perilaku hidup sehat dengan prestasi akademik mahasiswa keperawatan.